Supply matters for asset prices: Evidence from IPOs in emerging markets - Matías Braun; Borja Larrain (Federal Reserve Bank of Boston, 2006)
We show that the introduction of a new asset affects the prices of previously existing assets in a market. Using data from 254 IPOs in emerging markets, we find that stocks in industries that covary highly with the industry of the IPO experience a larger decline in prices relative to other stocks during the month of the IPO. The effects are stronger when the IPO is issued in a market that is less integrated internationally, and when the IPO is big. The evidence supports the idea that the composition of asset supply affects the cross-section of stock prices.
Keywords: G11; G14; G15; 330